Physiological Signaling Functions of Reactive Oxygen Species in Stem Cells: From Flies to Man - Sinenko, Sergey A.; Starkova, Tatiana Yu.; Kuzmin, Andrey A.; Tomilin, Alexey N. (Frontiers in Cell and Developmental Biology, 2021)
Reactive oxygen species (ROS), superoxide anion and hydrogen peroxide, are generated as byproducts of oxidative phosphorylation in the mitochondria or via cell signaling-induced NADPH oxidases in the cytosol. In the recent two decades, a plethora of studies established that elevated ROS levels generated by oxidative eustress are crucial physiological mediators of many cellular and developmental processes. In this review, we discuss the mechanisms of ROS generation and regulation, current understanding of ROS functions in the maintenance of adult and embryonic stem cells, as well as in the process of cell reprogramming to a pluripotent state. Recently discovered cell-non-autonomous ROS functions mediated by growth factors are crucial for controlling cell differentiation and cellular immune response in Drosophila. Importantly, many physiological functions of ROS discovered in Drosophila may allow for deciphering and understanding analogous processes in human, which could potentially lead to the development of novel therapeutic approaches in ROS-associated diseases treatment.